Real-world progression-free survival of first line afatinib patients with EGFR-mutant advanced lung adenocarcinoma: A multicentre study in Indonesia - Noni Novisari Soeroso; Elisna Syahruddin; Chaliza Soliha; Laksmi Wulandari; Ana Rima Setijadi; Sabrina Ermayanti; Suryanti Dwi Pratiwi; Andreas Infianto; Novita Andayani; Sri Melati Munir; Avissena Dutha Pratama; Ida Ayu Jasminarti Dwi Kusumawardani; et al. (Cancer Treatment and Research Communications)
Introduction: Afatinib, a second-generation EGFR tyrosine kinase inhibitor (TKI), has demonstrated clinical benefit in EGFR-mutant non-small cell lung cancer (NSCLC) through clinical trials. However, real-world data, particularly in Southeast Asian populations, remain limited. This study aimed to evaluate the real-world progression-free survival (PFS) of Indonesian patients with EGFR-mutant advanced lung adenocarcinoma treated with first-line afatinib. Methods: A retrospective cohort study was conducted using data from 1008 EGFR-positive NSCLC patients screened between 2019 and 2023 across 14 Indonesian centers. Of these, 215 received afatinib, and 105 patients met eligibility criteria. Clinical and demographic data, including EGFR mutation types and ECOG performance status, were collected. Kaplan-Meier and Cox regression analyses were used to assess PFS and associated factors. Results: The median age was 59 years; 54.3 % were female and 65.7 % never-smokers. Exon 19 deletion was the most common mutation (57.1 %), followed by L858R (29.5 %). Median PFS was 12.0 months. ECOG performance status significantly influenced PFS: patients with ECOG 0–1 had a median PFS of 13.0 months versus 8.0 months for ECOG ≥2 (HR = 0.44; p = 0.001). Other variables, including smoking status, stage, and brain metastases, were not significantly associated with PFS. Mutation subtype analysis revealed non-significant trends. Conclusion: ECOG performance status is a significant prognostic factor for PFS in patients treated with first-line afatinib. These real-world findings support its continued use and highlight the need for broader multicenter studies to validate the role of EGFR mutation subtypes in treatment outcomes.